2021
DOI: 10.1016/j.celrep.2020.108590
|View full text |Cite|
|
Sign up to set email alerts
|

Cell-Type-Specific Immune Dysregulation in Severely Ill COVID-19 Patients

Abstract: Recent studies have demonstrated immunologic dysfunction in severely ill COVID-19 patients. We use single-cell RNA sequencing (scRNA-seq) to analyze the transcriptome of peripheral blood mononuclear cells (PBMC) from healthy (n=3) and COVID-19 patients with moderate disease (n = 5), acute respiratory distress syndrome (ARDS, n = 6), or recovering from ARDS (n = 6). Our data reveal transcriptomic profiles indicative of defective antigen presentation and interferon responsiveness in monocytes from ARDS patients,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 85 publications
1
83
0
1
Order By: Relevance
“…Consistent with these findings, T cells isolated from the spleen of mice with DIO display altered mitochondrial phosphorylation and a preferential utilization of fatty acids as mitochondrial fuel. In COVID-19, T cells from patients with severe disease show an increased oxidative phosphorylation compared with mild or recovered groups, suggesting altered T cell metabolism in severe infection [ 98 ]. Furthermore, T cells from patients with progressed COVID-19 displayed an altered mitochondria morphology, increased mitochondrial mass and accumulation of ROS production.…”
Section: The Obesogenic Hostmentioning
confidence: 99%
“…Consistent with these findings, T cells isolated from the spleen of mice with DIO display altered mitochondrial phosphorylation and a preferential utilization of fatty acids as mitochondrial fuel. In COVID-19, T cells from patients with severe disease show an increased oxidative phosphorylation compared with mild or recovered groups, suggesting altered T cell metabolism in severe infection [ 98 ]. Furthermore, T cells from patients with progressed COVID-19 displayed an altered mitochondria morphology, increased mitochondrial mass and accumulation of ROS production.…”
Section: The Obesogenic Hostmentioning
confidence: 99%
“…Probably, the antiviral function of these CD8 + T cells is impaired by a defect in the priming process, or another possibility is that virusspecific CD8 + T cells have an excessive activation, which can affect the adequate function of the cells. On this sense, it has been reported that CD8+ T cells from severe COVID-19 patients display activation of IFN signaling that correlates with the disease severity, but contrary to the previous, Yao C et al identified that these CD8+ T cells (from severe COVID-19) have a gene expression profile related to a deficiency in cytotoxic function [55]. Severe COVID-19 patients have a reduced frequency of multi-functional CD4 + T cells (producers of at least two types of cytokines) and apparently, this functional damage predisposes to disease severity [53].…”
Section: What Do We Know About T Cells During Covid-19?mentioning
confidence: 90%
“…A multi-omics analysis of blood plasma collected from COVID-19 patients during the first week of infection following diagnosis revealed changes in the immune cell repertoire, increases in inflammatory markers and loss of metabolites and metabolic processes as the disease evolved from mild to moderate severity ( Su et al., 2020 ). A transcriptomics study characterized the single-cell RNA profile of peripheral mononuclear cells of COVID-19 patients, revealing defective antigen presentation in monocytes and high interferon responsiveness in lymphocytes, and suppression of genes involved in cytotoxic activity in both NK and CD8 lymphocytes, thus explaining the reduced viral clearance of severe COVID-19 patients ( Yao et al., 2020 ). Single-cell RNA-sequencing of host factors has also disclosed changes in cholesterol biosynthesis in the disease: increased cholesterol synthesis correlates with SARS-CoV-2 resistance ( Daniloski et al., 2020 ).…”
Section: Dysregulated Inflammatory Responses In Covid-19mentioning
confidence: 99%